(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
The aim of the paper is to examine the evolving legacy of epic in video games from a gender-sensitive perspective, identifying which elements of epic have been preserved and which have been transformed according to new identity-related patterns and perceptions. To this end, the essay undertakes a comparative analysis of some case studies. The selected videogames include God of War (2018), Horizon Zero Dawn (2017), and Hellblade. Senua’s Sacrifice (2017) and The Last of Us (2013). The analysis is based on the concept of the monomyth, as outlined by Joseph Campbell in The Hero with a Thousand Faces (1949), which describes common and recurring patterns that characterize the hero’s journey. Subsequently, the hero’s journey will be examined in God of War and The Last of Us, and then compared to the journeys of the two heroines in Horizon and Hellblade. Accordingly, the paper explores the construction of the character in accordance with the elements outlined by Campbell to trace the evolution of the hero or heroine in the video game industry through a gender-sensitive approach.